PENERAPAN CRITICAL PATH METHOD (CPM) DALAM MENGANALISIS MANAJEMEN WAKTU PADA PERENCANAAN IKLAN GMS DIGITAL MARKETING - Cynthia, Mayang Modelina; Cipta, Hendra; Lubis, Riri Syafitri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Planning helps monitor activities. to achieve the expected efficiency and effectiveness. In advertising planning at GMS Digital Marketing, there are often losses. The purpose of this study is to find out how to manage good time in advertising planning in GMS Digital Marketing and find out what efforts can be made so that advertising planning has efficient time. A mathematical approach called Critical Path Analysis (CPM) is used to organize the grouping of project operations. The project activities described using the CPM Method are a two-round procedure consisting of a forward and backward approach to setting a schedule when conducting a critical path analysis. ES and EF are set up during the forwarding process. During the transfer, LS and LF are determined. Early Start (ES) is the fastest way to start an activity. CPM is a cost-cutting approach for projects. We can know when costs and schedules need to be negotiated to meet project deadlines while keeping costs as low as possible. When a dimension is used, then CPM is used. (More accurate time estimates). Therefore, from the results of this study, a critical path is obtained that requires additional labor and time in completing the work